Volatile capital flows and financial integration : the role of moral hazard - Kikuchi, Tomoo (2020)
We study a model in which income and capital flows between countries are jointly determined in a world economy with integrated financial markets. In a setting that combines risky entrepreneurial activity with moral hazard, we find that a shift from autarky to financial integration leads to boom-bust cycles in capital flows, output and consumption. Moral hazard causes cycles because financial intermediaries incentivize effort by insisting entrepreneurs take an equity share in their own projects. The size of this stake rises with wealth, discouraging entrepreneurship and inhibiting capital formation. The reverse is true when wealth falls, generating cycles.